2019
DOI: 10.1128/jb.00614-18
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Selenite Reductase from Bacillus selenitireducens Strain MLS10

Abstract: The putative respiratory selenite [Se(IV)] reductase (Srr) from Bacillus selenitireducens MLS10 has been identified through a polyphasic approach involving genomics, proteomics, and enzymology. Nondenaturing gel assays were used to identify Srr in cell fractions, and the active band was shown to contain a single protein of 80 kDa. The protein was identified through liquid chromatography-tandem mass spectrometry (LC-MS/MS) as a homolog of the catalytic subunit of polysulfide reductase (PsrA). It was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 89 publications
0
22
0
Order By: Relevance
“…Protein representatives from DMSOR family lineages where the function of the enzyme was previously elucidated by biochemical, genetic, or structural methods were selected to be BLAST queries to construct a comprehensive library of sequences. For the families we analyzed, these included PsrA from W. succinogenes 35 , PhsA from S. enterica serovar Typhimurium 36 , SrrA from B. selenitireducens 37 , ArrA from Chrysiogenes arsenatis 82 and B. selenitireducens 83 , ArxA from A. ehrlichii 19 , TtrA from S. enterica sero- www.nature.com/scientificreports/ var Typhimurium 38 , SrdA from B. selenatarsenatis 39 , the arsenate reductase of P. aerophilum 40 , AioA from A. faecalis 84 and Rhizobium sp. NT-26 85 , FmdB from Methanosarcina barkeri 86 , FmdB and FwdB from Methanothermobacter wolfei 87 FdhG from E. coli 44 , D. gigas 45 , and D. desulfuricans 71 , FdhH from E. coli 46 , NAD-dependent formate dehydrogenases from Moorella thermoacetica 88 and Peptoclostridium acidaminophilum 68 , and the F 420 -dependent formate dehydrogenases of Methanococcus maripaludis 70 and M. vannielli 89 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein representatives from DMSOR family lineages where the function of the enzyme was previously elucidated by biochemical, genetic, or structural methods were selected to be BLAST queries to construct a comprehensive library of sequences. For the families we analyzed, these included PsrA from W. succinogenes 35 , PhsA from S. enterica serovar Typhimurium 36 , SrrA from B. selenitireducens 37 , ArrA from Chrysiogenes arsenatis 82 and B. selenitireducens 83 , ArxA from A. ehrlichii 19 , TtrA from S. enterica sero- www.nature.com/scientificreports/ var Typhimurium 38 , SrdA from B. selenatarsenatis 39 , the arsenate reductase of P. aerophilum 40 , AioA from A. faecalis 84 and Rhizobium sp. NT-26 85 , FmdB from Methanosarcina barkeri 86 , FmdB and FwdB from Methanothermobacter wolfei 87 FdhG from E. coli 44 , D. gigas 45 , and D. desulfuricans 71 , FdhH from E. coli 46 , NAD-dependent formate dehydrogenases from Moorella thermoacetica 88 and Peptoclostridium acidaminophilum 68 , and the F 420 -dependent formate dehydrogenases of Methanococcus maripaludis 70 and M. vannielli 89 .…”
Section: Methodsmentioning
confidence: 99%
“…We focused on a number of lineages beyond ArxA/ArrA and AioA. Phylogenetic analyses have consistently found that ArxA/ArrA is closely related to a lineage comprised of the catalytic subunits of the respiratory polysulfide reductase of Wolinella succinogenes (PsrA) 35 , thiosulfate reductase of Salmonella enterica serovar Typhymurium (PhsA) 36 , and selenite reductase of Bacillus selenitireducens (SrrA) 37 , as well as a lineage comprised of the catalytic subunits of the respiratory tetrathionate reductase of S. eneterica serovar Typhymurium (TtrA) 38 , the selenate reductase of B. selenatarsenatis 39 , and the arsenate reductase of the archaeon Pyrobaculum aerophilum 40 , whilst AioA is more closely related to formate dehydrogenase N catalytic subunits (FdhG) 1,[24][25][26] . Rigorous phylogenetic analyses of these DMSOR members and closely related lineages has revealed several novel insights into the evolution of DMSORs.…”
mentioning
confidence: 99%
“…For PSCT_04485, the putative [3Fe-4S]-binding motif and the cysteine residue predicted to coordinate the guanine dinucleotide molybdopterin cofactor are highlighted in pink and cyan respectively. The cysteine residue was identified by aligning the IdrA sequence with those of the periplasmic nitrate reductase (NapA) of Desulfovibrio desulfuricans (Dias et al, 1999) and selenite reductase (SrrA) of Bacillus selenitireducens (Wells et al, 2019). For PSCT_04484, the putative twin arginine translocation motif and the predicted [2Fe-2S]-binding motif are highlighted in green and yellow, respectively.…”
Section: Comparative Proteomic Analysis Of Strain Sct Grown On Iodatementioning
confidence: 99%
“…Elemental selenium was deposited both inside and outside of the cells. B. selenitireducens produced enzymes to reduce the oxidized forms of arsenic and selenium to their less toxic reduced forms (Wells et al, 2019 ). B. cereus CM100B and B .…”
Section: Role Of Bacillus Species In Biodegradatiomentioning
confidence: 99%